The students mathematics motivation scale: a measure of intrinsic, extrinsic, and perceptions of mathematics - Nurkarim, Arfi Wahyu; Qonita, Wilda; Monterroza, David (International Journal on Teaching and Learning Mathematics, 2023)
Students' mathematical motivation is an important factor in understanding mathematics. Many studies have shown that students who have high motivation to learn mathematics, get better achievement than students who have low motivation. However, research that provides instruments to measure the mathematics motivation scale is still rare. This research aims to: (1) Describe the process of developing the Student Mathematics Motivation Scale (SMMS) instrument, (2) Describe the results of developing the Student Mathematics Motivation Scale (SMMS) instrument. This research model uses survey research with mixed methods. The research subjects were Junior High School students in MTs. 2 Nurul Islam, Mojokerto, Indonesia. This research produced 19 questions containing 3 main indicators, they are intrinsic goals, extrinsic goals, and perceptions of mathematics. The validity test results show a very good level of validity, as well as a high category of reliability (α = 0.817). Therefore, this instrument is very good for measuring students’ mathematics motivation scale.